2015
DOI: 10.1007/s11999-015-4264-3
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Dislocation of the Hip Successfully Treated by Preoperative Traction and Medial Open Reduction: A 22-year Mean Followup

Abstract: Background During the last 35 years, the medial approach has been reported more frequently than the anterior approach for open reduction of developmental dislocation of the hip (DDH), however, few studies have followed children treated by medial open reduction to adulthood. Questions/purposes The purposes of our study were: (1) to assess the development of 71 completely dislocated hips after medial open reduction, the incidence of additional surgery and avascular necrosis during the followup period, and the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
18
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 86 publications
3
18
1
2
Order By: Relevance
“…AVN rates after open reduction using the posteromedial limited approach are between 0% and 66% in the literature 10 . In their study of long-term results of open reduction using the posteromedial limited approach, Farsetti et al mentioned that they observed an AVN rate of 18% after 22 years of follow-up 20 . In our study, osteonecrosis rates were 17% for both male and female patients.…”
Section: Discussionsupporting
confidence: 53%
“…AVN rates after open reduction using the posteromedial limited approach are between 0% and 66% in the literature 10 . In their study of long-term results of open reduction using the posteromedial limited approach, Farsetti et al mentioned that they observed an AVN rate of 18% after 22 years of follow-up 20 . In our study, osteonecrosis rates were 17% for both male and female patients.…”
Section: Discussionsupporting
confidence: 53%
“…Group 3 consisted of 11 patients (18 hips) who were 25 to 36 months old at the time of operation, equaling 25% of all hips in the study. The authors observed avascular necrosis in 44% of these hips [1]. This rate is higher than the other groups in the study.…”
contrasting
confidence: 46%
“…In their study, the age groups lack homogenity. We also found patient selection bias [1]. Group 3 consisted of 11 patients (18 hips) who were 25 to 36 months old at the time of operation, equaling 25% of all hips in the study.…”
mentioning
confidence: 91%
“…Среди распространенных методов хирургической коррекции выделяют реконструктивные вмешательства на впадине сустава (остеотомии таза), реконструктивные вмешательства на бедренном компоненте (межвертельные остеотомии) [19]. Открытое вправление применяют при тяжелой степени патологии (вывих) для транспозиции головки в естественную впадину, часто дополняют реконструкцией впадины, иногда -бедра [15,20].…”
unclassified
“…Среди дегенеративных заболеваний, приобретенных в период роста, наиболее распространена болезнь Легга -Кальве -Пертеса [20]. БЛКП представляет собой идиопатический остеонекроз головки бедра с последующими осложнениями в виде деформации и развития остеоартроза [20]. Заболевание часто встречается у детей в воз- Ортопедия, травматология и восстановительная хирургия детского возраста.…”
unclassified